IMPLEMENTASI PEMBELAJARAN RENANG TRADISIONAL DAN KOREKSI GERAK START JONGKOK MELALUI MEDIA VIDEO SLOW MOTION - Isti Qomah Rachman; Abu Bakar; Sanjung Sederhana; Metusala Aprilando Weanglia; La Robi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning the crouch start technique in physical education requires movement precision and strong visual understanding. However, traditional swimming instruction, which is dominated by direct demonstrations and verbal explanations, often fails to provide optimal movement feedback. This study aims to examine the effect of using slow-motion video media in traditional swimming instruction on students’ learning motivation in the crouch start technique material. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects of the study consisted of 33 students from the Physical Education Study Program at Universitas Muhammadiyah Sorong. The research instrument was a learning motivation questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive statistics, correlation analysis, and paired sample t-test with a significance level of 0.05. The results showed an increase in the average score of students’ learning motivation from 61.12 in the pretest to 77.18 in the posttest. The paired sample t-test results indicated a significant difference between the pretest and posttest (Sig. 0.000 < 0.05). Therefore, it can be concluded that the use of slow-motion video-based learning media has a significant effect on improving students’ learning motivation in the crouch start technique material. Slow-motion video media are effective as a visual tool to support the learning of complex movement techniques in a more engaging, systematic, and meaningful way.